Applying educational psychology in coaching athletes - Huber, Jeffrey J. (Human Kinetics, 2013)
Discusses how to improve coaching success and athletic performance through the application of teaching principles and theories. This book provides insight into the principles of psychology that drive the emotions, motivation, expectations, self-worth and relationships of athletes.